Evaluation and Management of Proximal Humerus Fractures - Ekaterina Khmelnitskaya; Lauren E. Lamont; Samuel A. Taylor; Dean G. Lorich; David M. Dines; Joshua S. Dines (Advances in Orthopedics)
Proximal humerus fractures are common injuries, especially among older osteoporotic women. Restoration of function requires a thorough understanding of the neurovascular, musculotendinous, and bony anatomy. This paper addresses the relevant anatomy and highlights various management options, including indication for arthroplasty. In the vast majority of cases, proximal humerus fractures may be treated nonoperatively. In the case of displaced fractures, when surgical intervention may be pursued, numerous constructs have been investigated. Of these, the proximal humerus locking plate is the most widely used. Arthroplasty is generally reserved for comminuted 4-part fractures, head-split fractures, or fractures with significant underlying arthritic changes. Reverse total shoulder arthroplasty is reserved for patients with a deficient rotator cuff, or highly comminuted tuberosities.